2015
DOI: 10.5847/wjem.j.1920-8642.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sedation on short-term and long-term outcomes of critically ill patients with acute respiratory insufficiency

Abstract: Sedation was associated with in-hospital death. The patients who had received sedation had a longer duration of ventilation, a longer stay in intensive care unit and in hospital, and an increased in-hospital mortality rate compared with the patients who did not receive sedation. Compared with daily interruption or light sedation, deep sedation increased the in-hospital mortality and decreased the 60-month survival for patients who had received sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…While Kress et al's [11] study found no relationship between DSI and PTSD there was no incidence of PTSD, some studies [12,13] with a focus on shorter and long term outcomes such as delirium and PTSD have similarly found no relationship between these conditions and DSI up to 12 months and other studies [4,9] have found differing results. However, all these studies only provide anecdotal evidence.…”
Section: Introductionmentioning
confidence: 63%
“…While Kress et al's [11] study found no relationship between DSI and PTSD there was no incidence of PTSD, some studies [12,13] with a focus on shorter and long term outcomes such as delirium and PTSD have similarly found no relationship between these conditions and DSI up to 12 months and other studies [4,9] have found differing results. However, all these studies only provide anecdotal evidence.…”
Section: Introductionmentioning
confidence: 63%
“…Careful respiratory monitoring and administrating enough sedatives are recommended to prevent early unplanned SE in an inapposite time. all previous studies on this subject have been performed in general ICUs while our patients are OP-poisoned with severe respiratory effects [4].…”
Section: Resultsmentioning
confidence: 99%
“…Although Bambi, et al [7] believed that SE could be prevented with non-benzodiazepines drugs, use of BZDs is strongly recommended for OP poisoning [4,20]. Use of physical restrains without prescription of sedative drugs has not been recommended since it can be a risk factor for SE [7].…”
Section: Sedative Physical Restraint and Agitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in obese patients, whose pulmonary compliance is already reduced, we recognize a favorable outcome in awake or mildly sedated patients in our clinical practice. Data from large multi-centered cohorts is still needed, but several studies acquired from single centered patient groups (n ¼ 140 patients; n ¼ 91 patients) indicate that a reduction or cessation of sedation in critically ill patients irrespective of body weight is associated with a shorter duration of mechanical ventilation, a shorter stay in the ICU and in hospital generally as well as a decreased in-hospital mortality [26,27]. In order to implement a protocol of no sedation in clinical practice, early tracheotomy may reduce stress and agitation in critically ill patients receiving mechanical ventilation.…”
Section: Sedative Drugs Muscle Relaxants and Early Tracheotomymentioning
confidence: 99%